Rebound (reactive) thymic hyperplasia after chemotherapy in children with lymphoma - Ashraf Fouda; Shaimaa Kandil; Gihad Hamid; Khadijah Boujettif; Mohamed Mahfouz; Mohamed Abdelaziz (Elsevier, 2019)
Introduction: Thymic regrowth after chemotherapy treatment has been reported in children with lymphoma, and in order to avoid misdiagnosing these cases as relapses, physicians should become familiar with rebound (reactive) thymic hyperplasia (RTH) and remain aware of its possible occurrence. We aimed to estimate the prevalence of RTH in children with lymphoma after completion of chemotherapy and to evaluate the clinical characteristics, outcomes, and the findings of computed tomography (CT) and gallium-67 (GA-67) scans in these patients. Patients and methods: We conducted a retrospective cross-sectional study by reviewing the health records of children with a lymphoma diagnosis managed at an outpatient paediatric oncology clinic in Jeddah, Saudi Arabia. Results: Rebound thymic hyperplasia was detected in 51.9% of the lymphoma patients (14/27). It developed a median of 2.5 months after completion of chemotherapy (range, 2.0-4.25 months). Patients with RTH had significantly shorter treatment durations, and we found no significant differences between patients with and without RTH in sex, age at diagnosis, type of lymphoma or type of treatment received. All patients with RTH were asymptomatic, and routine laboratory tests did not detect any abnormalities in them. The findings of CT and GA-67 scans were highly suggestive of RTH. None of the patients with RTH had a recurrence, and RTH resolved spontaneously within a median of 6 months (range, 4.0-11.0 months). Conclusion: RTH was detected in ∼50% of children with lymphoma after completion of chemotherapy. A clinical evaluation and laboratory tests combined with imaging by CT and GA-67 can help identify RTH and rule out other lesions elsewhere. Resumen: Introducción: Se ha descrito la regeneración del timo tras la quimioterapia en niños con linfoma y, para evitar diagnosticar incorrectamente estos casos como recurrencias, los facultativos han de familiarizarse con la hiperplasia tímica de rebote (HTR) y tener en consideración su posible ocurrencia. Nuestro objetivo fue estimar la prevalencia de HTR en niños con linfoma tras la quimioterapia y evaluar las características clínicas, evolución y hallazgos de las pruebas de imagen mediante tomografía computarizada (TC) y la gammagrafía con galio 67 (GA-67). Pacientes y métodos: Estudio retrospectivo transversal, mediante la revisión de las historias clínicas de niños diagnosticados de linfoma, realizado en la Clínica Ambulatoria de Oncología Infantil del Centro de Oncología de Yeda, Arabia Saudita. Resultados: Se detectó HTR en el 51,9% de los pacientes con linfoma (14/27 pacientes). La HTR ocurrió una mediana de 2,5 meses tras finalizarse el tratamiento (rango: 2,0-4,25 meses). Los pacientes con HTR recibieron tratamientos significativamente más cortos, y no se observaron diferencias entre pacientes con y sin HTR en cuanto al sexo, la edad al diagnóstico, el tipo de linfoma o el tipo de tratamiento recibido. Todos los pacientes con HTR se encontraban asintomáticos y las pruebas rutinarias de laboratorio no evidenciaron alteraciones. La TC y la GA-67 fueron altamente sugestivas de HTR. Ninguno de los pacientes con HTR tuvieron recurrencias y la HTR se resolvió espontáneamente en una mediana de 6 meses (rango: 4,0-11,0 meses). Conclusión: Se detectó HTR en alrededor del 50% de los niños con linfoma tras completarse el tratamiento. La evaluación clínica, pruebas de laboratorio, TC y gammagrafía con GA-67 resultan útiles para identificar la HTR y descartar otras lesiones en otras localizaciones.